Persecution and Migrant Self-Selection: Evidence from the Collapse of the Communist Bloc - Abramitzky, Ran; Baseler, Travis; Sin, Isabelle (The Review of Economics and Statistics, 2024)
Abstract How does persecution affect who migrates? We analyze migrants' self-selection out of the USSR and its satellite states before and after the collapse of Communism using census microdata. We find that migrants arriving before and around the time of the collapse (who were more likely to have moved because of persecution) were more educated and obtained better labor market outcomes than those arriving later. This change is not fully explained by the removal of Communist-era emigration restrictions. Instead, we show both theoretically and empirically that this pattern is consistent with more positive self-selection of migrants who are motivated by persecution.